The Ubiquitin-Conjugating DNA Repair Enzyme HR6A Is a Maternal Factor Essential for Early Embryonic Development in Mice - Roest, Henk P. (American Society for Microbiology, 2004)
The Saccharomyces cerevisiae RAD6 protein is required for a surprising diversity of cellular processes, including sporulation and replicational damage bypass of DNA lesions. In mammals, two RAD6-related genes, HR6A and HR6B, encode highly homologous proteins. Here, we describe the phenotype of cells and mice deficient for the mHR6A gene. Just like mHR6B knockout mouse embryonic fibroblasts, mHR6A-deficient cells appear to have normal DNA damage resistance properties, but mHR6A knockout male and female mice display a small decrease in body weight. The necessity for at least one functional mHR6A (X-chromosomal) or mHR6B (autosomal) allele in all somatic cell types is supported by the fact that neither animals lacking both proteins nor females with only one intact mHR6A allele are viable. In striking contrast to mHR6B knockout males, which show a severe spermatogenic defect, mHR6A knockout males are normally fertile. However, mHR6A knockout females fail to produce offspring despite a normal ovarian histology and ovulation. The absence of mHR6A in oocytes prevents development beyond the embryonic two-cell stage but does not result in an aberrant methylation pattern of histone H3 at this early stage of mouse embryonic development. These observations support redundant but dose-dependent roles for HR6A and HR6B in somatic cell types and germ line cells in mammals.